2008
DOI: 10.1007/s00221-008-1495-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical excitability changes following grasping exercise augmented with electrical stimulation

Abstract: Rehabilitation with augmented electrical stimulation can enhance functional recovery after stroke, and cortical plasticity may play a role in this process. The purpose of this study was to compare the effects of three training paradigms on cortical excitability in healthy subjects. Cortical excitability was evaluated by analysing the input-output relationship between transcranial magnetic stimulation intensity and motor evoked potentials (MEPs) from the flexor muscles of the fingers. The study was performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 43 publications
8
96
0
1
Order By: Relevance
“…The duration of SP in healthy humans is linearly related to the stimulus intensity and it is generated by both the intracortical and peripheral mechanisms and, in addition, it is altered in several neurologic diseases (Barsi et al 2008;Daskalakis et al 2008;Säisänen et al 2008). In the present study, the SP durations remained unaffected throughout the study in both hemispheres and in both groups while the MEP latencies shortened in FET group.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The duration of SP in healthy humans is linearly related to the stimulus intensity and it is generated by both the intracortical and peripheral mechanisms and, in addition, it is altered in several neurologic diseases (Barsi et al 2008;Daskalakis et al 2008;Säisänen et al 2008). In the present study, the SP durations remained unaffected throughout the study in both hemispheres and in both groups while the MEP latencies shortened in FET group.…”
Section: Discussionsupporting
confidence: 46%
“…This suggests that FET had a specific excitatory effect in the neural circuitry controlling affected hand muscles having no measurable effect on the inhibitory cortical circuitry in these subjects. Previous studies assessing the effects of functional electrical stimulation (FES) in healthy subjects have similarly failed to show any effect on SP duration even though they have shown excitability changes in MEPs also after very short FES exposures (Kido Thompson and Stein 2004;Barsi et al 2008). It is likely that the corticospinal excitability and the control of cortical inhibition are dissociated in their response to peripheral functional electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the combination of a motor task (swallowing) with functional electrical stimulation (PES) was ineffective. Earlier research regarding hand and leg rehabilitation using motor training with sensory stimulation suggested that that this type of combined stimuli can induce larger changes in excitability and/or neuroplasticity in motor cortex [39][40][41] , whereas tongue protrusion motor training, which alone produces measured neuroplasticity and successful performance, was less effective on motor cortex with nociceptive sensory stimulation. 42 These may be due to the differences in the neural systems between spinal and cranial nerves or in the type of experimental noxious stimulus.…”
Section: Changes In the Corticobulbar Neural Circuitmentioning
confidence: 99%
“…induce plasticity in the motor cortex and to be an effective approach in rehabilitation after stroke [6].…”
Section: Introductionmentioning
confidence: 99%